Cleft lip and palate transmembrane protein 1-like is a putative regulator of tumorigenesis and sensitization of cervical cancer cells to cisplatin - Liu, Weipeng; Huang, Fengdan; Yao, Yueting; Liang, Yan; Yan, Zhiling; Guo, Lili; Zhang, Xinwen; Shi, Li; Yao, Yufeng (Frontiers in Oncology, 2024)
BackgroundCervical cancer stands as one of the leading causes of cancer-related mortality in women worldwide, yet the precise functions of host genes implicated in its pathogenesis remain elusive. Genome-wide association studies (GWAS) have revealed a significant association between the CLPTM1L locus and cervical cancer risk in European women, and aberrant expression of CLPTM1L has been noted in various malignant tumors. However, the role of CLPTM1L in cervical cancer remains largely unexplored.MethodsThe expression of CLPTM1L in cervical cancer cells and tissues was detected by RT-qPCR. Furthermore, the potential biological functions of CLPTM1L in the context of cervical cancer were explored via RNA sequencing. Cell proliferation rates and the responsiveness of cervical cancer cells to cisplatin were evaluated using the CCK-8 assay, while cell apoptosis was quantified through the utilization of flow cytometry. Nude mouse xenograft models were utilized to explore the impact of CLPTM1L on tumor formation in vivo.ResultsOur findings demonstrated a significant increase in CLPTM1L mRNA expression levels in HeLa and C33A cells, as well as in cervical carcinoma tissues, compared to ECT1/E6E7 cells and adjacent normal tissues. Genes related to CLPTM1L were found to be enriched in the Hedgehog signaling pathway. In vitro and in vivo studies showed that reducing CLPTM1L expression markedly inhibited cell proliferation via downstream candidate genes BOC and LRP2. Furthermore, the downregulation of CLPTM1L was found to enhance cisplatin-induced cell apoptosis and increase the susceptibility of cervical cancer cells to cisplatin through DAP1.ConclusionsCLPTM1L could impact cervical cancer cell proliferation and cisplatin-induced cell apoptosis, as well as cisplatin susceptibility in cervical cancer cells. This investigation has bestowed upon us novel insights into the pathogenesis of cervical cancer, underscoring the potential of CLPTM1L as a promising target for chemotherapeutic sensitization in the management of this malignancy.